POTENCIALIDADES DE UMA SEQUÊNCIA DE ENSINO INVESTIGATIVA PARA O ENSINO DO OBJETO DE CONHECIMENTO ‘PLANTAS’ PARA OS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Brutti, Marilene dos Reis (2024)
This study is part of the research line Teaching and Learning of Science and Mathematics, within the Professional Master's Program in Science and Mathematics Teaching at the Franciscan University. It encompasses the study of the knowledge object 'Plants' which should be addressed along with the second-year elementary school students, according to the National Common Curricular Base (BNCC). The document highlights the need to explore the diversity of plants by identifying their parts, characteristics, and functions, as well as recognizes the importance of environmental preservation and biodiversity. However, it has been observed that, in general, the study of the knowledge object 'Plants' has not awakened in students its true purpose, which should be the recognition of plants’ diversity and their importance in the ecosystem as living beings that ensure the survival of all other life forms on the planet. Thus, the objective of this study was to investigate the potential of an investigative teaching sequence for teaching the knowledge object 'plants' to early elementary school students. For this purpose, a teaching sequence was developed, based on the assumptions of the Didactic Approach of Inquiry-Based Teaching, particularly considering the key activities proposed by Carvalho (2018), which are: the presentation of a contextualized problem, the systematization of knowledge, the contextualization of knowledge, and the evaluation. Additionally, an initial activity was included to address the analysis of students' prior knowledge. The teaching sequence, composed of eight activities carried out over seven meetings totaling 12 class hours, was applied to a class of 23 second-year elementary school students from a municipal public school located in Santa Maria/RS. The data for analyzing the effectiveness of the developed teaching sequence were collected from all student productions and the records of the researcher and the class teacher. In general, a significant increase in information and evidence of knowledge expansion by the students was observed. Such evidence was noted through several aspects, including the expansion of information represented in drawings, greater precision of information about the species addressed in the different activities of the didactic sequence, and more assertive presentation of the information. These observations indicate notable progress in the understanding and assimilation of the contents worked on throughout the proposed activities. The developed teaching sequence constitutes an educational product entitled 'Teaching Sequence for the Study of Plants in the Early Years of Elementary School,' which will be made available in the format of an E-book on the page of the Post Graduate Program in Science and Mathematics Teaching (PPGECIMAT) and also on the EduCAPES Portal.